Awareness of Sustainable Development Goals among Students from a Chinese Senior High School - Xinqun Yuan; Le Yu; Hao Wu (MDPI AG, 2021)
Education is an essential component of the Sustainable Development Goals (SDGs). Through a questionnaire survey among students from a Chinese senior high school, this study measured the self-reported knowledge, sources of information, learning situations, priorities, the impact of personal life and career planning with respect to the SDGs to understand their cognition, learning motivation and social readiness. The results show that students' knowledge and information sources in relation to the SDGs are limited, and there is no significant difference between boys and girls in relation to their knowledge of the SDGs, the source of information, the learning level of the SDGs, impact of personal life on the SDGs and career planning related to the SDGs. It is also shown that students have a better understanding of the number of the SDGs and the countries to which the SDGs are addressed and students receive information about the SDGs via formal education and traditional media. Regarding the penetration of the SDGs in course subjects, Chinese and native culture, foreign language, biology and geography have included all the SDGs. Through an analysis of responses and popularity rates, gender equality, quality education, reduced inequalities, no poverty, zero hunger, good health and well-being are shown to be the students' priorities with higher attention rates. Gender equality, quality education, clean water and sanitation are the top three goals in relation to which students consider that their personal life can have a greater impact. Students prefer to adopt the SDGs (decent work and economic growth, quality education, industry, innovation and infrastructure, sustainable cities and communities) as their personal career choice in the future. Suggestions for improving the implementation of Education for Sustainable Development (ESD) include comprehensive formal and non-formal education, publicity and curriculum integration to promote learning about the SDGs. A model of ESD in the school surveyed is presented for practical application. Based on this research, guidance and suggestions are provided to enhance students' awareness, knowledge and competencies in relation to sustainability and to encourage student engagement in global sustainable development.